Kakapo rescue : saving the world's strangest parrot - Montgomery, Sy (Scientists in the field., 2010)
On remote Codfish Island off the southern coast of New Zealand live the last 91 kakapo parrots on earth. Originally this bird numbered in the millions before humans brought predators to the islands. Now on the isolated island refuge, a team of scientists is trying to restore the kakapo population.